(untitled) (Baghdad Science Journal, 2025)
Uranium concentrations in soil were determined for ten locations in Salahdin governorate using CR-39 track detector, fission fragments track technique was used, the nuclear reaction of nuclear fission fragments obtained by the bombardment of 235U with thermal neutrons from (Am-Be) neutron source with flux (5000n.cm-2.s-1), the concentration values were calculated by a comparison with standard samples. The results of the measurements show that the uranium concentration in soil samples various from 0.42±0.018ppm in Beji province to 0.2±0.014 ppm in Tooz province with an average (0.31±0.08ppm), the values of uranium concentration in all samples are within the permissible limits universally.